Implementasi Metode Analytical Hierarchy Process dalam Pemilihan Tempat Wisata di Sukabumi - Tanu Kusnadi, Irwan (STMIK KAPUTAMA, 2023)
Sukabumi is one of the regencies in West Java Province which has many tourist attractions, both natural tourist attractions and artificial tourist attractions or recreational parks. Based on data owned by the Tourism Office in Sukabumi, it was recorded that in 2020 Sukabumi had the number of domestic tourists reaching 846,168 people and 686 foreign tourists. With so many tourist attractions in Sukabumi, tourists have many alternative criteria in choosing tourist attractions in Sukabumi. Based on the existing problems, these problems can be overcome by creating a Decision Support System using the Analytical Hierarchy Process (AHP) method. The selected tourist sites are Padlock Cinta, Karang Hawu Beach, Ciletuh Geopark, Situ Gunung, and Mount Tumpeng. By using the AHP method, it is hoped that it can help tourists choose tourist attractions in Sukabumi.